Use of Technology in Social Studies Teachıng: The Journey of Five Teachers - Erdi ERDOGAN; Buket SEREFLI (Anı Publishing, 2021)
This study aims to examine the effect of personal experiences of Social Studies teachers on using technology in the teaching process. The study was carried out with narrative research that is one of the qualitative research models. A purposeful sampling method was used in determining the study group. Five Social Studies teachers were included in the study. The research data were collected with a semi-structured interview form. Three sessions of interviews were conducted to collect research data. In the data analysis, narrative analysis was used to form the participants' stories, and thematic analysis was used to present the findings from the participant stories systematically. The findings revealed that Social Studies teachers have limited technological opportunities in their learning process; they could not access sufficient equipment during their undergraduate education. Still, despite these limited opportunities, they can develop their technology use skills in line with their interests and curiosities after starting their professional life. Besides, Social Studies teachers with more years of professional experience are willing to realise and eliminate their shortcomings, and cooperate. Thus they use instructional technologies effectively.